2019
DOI: 10.1093/ajcn/nqy261
|View full text |Cite
|
Sign up to set email alerts
|

Restricting carbohydrates at breakfast is sufficient to reduce 24-hour exposure to postprandial hyperglycemia and improve glycemic variability

Abstract: Background The breakfast meal often results in the largest postprandial hyperglycemic excursion in people with type 2 diabetes. Objective Our purpose was to investigate whether restricting carbohydrates at breakfast would be a simple and feasible strategy to reduce daily exposure to postprandial hyperglycemia. Design Adults with physician-diagnosed type 2 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 44 publications
2
32
0
9
Order By: Relevance
“…Moreover, previous studies have shown that the type and amounts of foods consumed, including at breakfast, may have effects on glucose metabolism hours after consumption. 18 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies have shown that the type and amounts of foods consumed, including at breakfast, may have effects on glucose metabolism hours after consumption. 18 19 …”
Section: Discussionmentioning
confidence: 99%
“…As observed in our study, the morning glucose excursion also corresponds to the largest glycemic peak across the day. Controlled feeding studies 18–21 have reported that lowering postbreakfast glycemic responses improves glucose variability, suggesting that the early glucose peak is critical to the overall dysglycemia across the day. In free-living people with T2D, glycemic responses are superimposed on numerous internal (ie, chronobiological mechanisms) and external (eg, habitual diet quality, medications, physical activity, social, and emotional) factors which influence glucose levels and variability.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies included in the analysis compared reduced carbohydrate content with higher carbohydrate content meals and showed that reducing the amount of carbohydrates of a meal results in a lower GL of that meal, and therefore better glycemic control [ 24 , 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent randomized crossover trial, Chang et al [ 25 ] investigated the effect of altered nutrient breakfasts on postprandial glucose response, but instead of altering GI through replacement of high-GI foods with low-GI ones, they altered GL by reducing the total amount of carbohydrate, resulting in a low-carbohydrate breakfast (LCBF). In the LCBF, carbohydrates provided approximately 10% of energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation